Implikasi Penerapan Fintech dan Blockchain Terhadap Profitabilitas Bank : Peran Moderasi Efisiensi keuangan - Muhammad Khoirul Sholikin; Liana Mangifera (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of fintech and blockchain implementation on banking profitability with financial efficiency as a moderating variable. A quantitative research approach was employed, involving a population of 105 banks registered with the Financial Services Authority (OJK). The sample was selected using purposive sampling, focusing on commercial banks with complete financial reports and evidence of blockchain adoption, resulting in five banks as research samples. The study utilized secondary data obtained from financial statements and official banking publications collected through documentation techniques. Fintech was measured based on the implementation of digital banking services, blockchain adoption was identified through disclosures in annual reports, financial efficiency was measured using the BOPO ratio, and profitability was proxied by Return on Assets (ROA). Data analysis included descriptive statistics, classical assumption tests, multiple linear regression, and Moderated Regression Analysis (MRA), processed using SPSS version 26 with a 5% significance level. The results indicate that fintech has a significant positive effect on banking profitability, while blockchain implementation does not have a significant effect. Furthermore, financial efficiency is not proven to moderate the relationship between fintech or blockchain and banking profitability.